Diseño de un sistema de control de inventarios para la empresa TRIALMECH CIA. LTDA, ubicada en la provincia de Pichincha, cantón Rumiñahui, parroquia Sangolquí - Bungacho Ganchala, Diego Andrés (2022)
The present integrative project was developed in the Company “Trialmech Cía. Ltda." dedicated to the design, production, installation, maintenance and sale of refrigeration systems, air conditioning, industrial refrigeration and automotive mechanical ventilation; the problem of the entity lies in the lack of an inventory control system, in the absence of policies and procedures established for the management of their stocks, stock levels, rotation and storage, as well as in the commercial process purchases and sales, the lack of inventory management, does not allow the company to have a reliable value of the cost of their stocks. Therefore, the objective of the project is to implement an inventory control system in the company Trialmech Cia. Ltda., located in the parish of Sangolquí, through the analysis of merchandise management, for the optimization of business resources. The methodology applied is based on a quantitative approach through a descriptive, field and analytical research; techniques such as the survey, interview and direct observation and instruments such as the structured questionnaire, interview guide and observation guide were used, directed to the technical manager, automotive mechanic technician, warehouse manager, warehouse assistant and accountant, as well as for the inventory survey; the information obtained through the development of the research allowed implementing an inventory control system for the analysis of the weighted average valuation method, considering the needs of the company. The inventory control system consists of a manual containing policies, procedures and financial indicators, which help to optimize economic resources; subsequently, the systematization was implemented in Excel (Visual Basic) to determine and calculate the real value of inventories of raw materials, supplies and finished product. It was recommended to the company to keep active the application of the inventory control system in future periods, for obtaining results that contribute to the improvement of its management, business development and competitiveness in the market